Industrial Estates in Central Clydeside - Verbreitung, Differenzierung und Bedeutung für den Strukturwandel eines alten Industrieraumes - Hommel, Manfred (ERDKUNDE, 1979)
Until now industrial estates are pretty rare in West Germany, but are recently proposed as an instrument to promote industrial change in the Ruhr coalfield. This paper examines industrial estates as an instrument of regional policy and their role in the modernization process of Central Clydeside. Four types of industrial estates: SIEC, New Town, private, and local authority estates are identified and described by number, size, and distribution. The objectives of the different developing agencies, location patterns, design, and factory types of their estates and their particular conditions and restrictions for incoming firms are analysed as well as the resulting differences in the industrial structure (by SIC order, size, density of employment, and ultimate ownership of establishments) and the intra-regional effects of the estates. The large government estates have attracted a lot of new industries - the SIEC estates mainly larger firms from outside the region, the New Town estates often smaler firms from Glasgow -, but due to their location in the older problem areas at the fringe of Glasgow and in Lanarkshire, Glasgow with its still declining industries has not as much participated in this growth as the outer parts of the conurbation. The recently developed small private and local authority estates are concentrated in the industrial core of the conurbation and encourage expanding local firms to stay there, so reducing industrial decline. Due to their variety and the cooperation of the different developing agencies industrial estates are an effective instrument not only for regional economic policy, but also for urban planning in old industrial regions.